Analisis Perbandingan Novel Dan Film 5 CM Serta Implikasinya Terhadap Pembelajaran Bahasa Indonesia Di SMA - Mulidi, Slamet; Rusly, Fathullah; Hamdiah, Magfirotul (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
Ecranisation is the process of civilizing novels into films. This embody or realization to the imagination of the reader who initially enjoyed work through visual media and then became audio-visual. This makes viewers more likely to compare the content of the novel and the story presented in a movie adapted to the novel. It required a study with the purpose of comparing the two objects. The study examined the convergence between two separate works with similar titles of novel and 5 cm film. The aim of this study is to produce discharges, additions and varications that appear in novels and 5 cm. It's a qualitative study with a descriptive type. The data in this study isa plot, a character and background that are undergoing an extropation in a 5 cm movie and novel. The source of the data in this study is donny's five-centimeter novel and a 5 cm movie accessed through the video. The technique for collecting data in this study is to use through the various stages of reading, reviewing, recording, data classification and data description. Then the data was analysed through the process of condensing data and progressing at the data presentation stageKeywords: Novel, Movie, Ecranisation